2018
DOI: 10.1038/s41598-018-31336-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influencing factors of overweight and obesity in a Chinese rural population: the Henan Rural Cohort Study

Abstract: The study aimed to estimate prevalence and influencing factors of overweight, general obesity, and abdominal obesity in rural areas of China. A total of 39034 participants aged 18 to 79 years were enrolled from the Henan Rural Cohort Study for the cross-sectional study. The age-standardized prevalence of overweight, general obesity, and abdominal obesity were 34.97%, 16.82%, and 43.71% in the general Chinese rural adults, respectively. Gender differences were: 36.04%, 18.98%, 35.37% for men, and 34.55%, 15.42%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 19 publications
3
45
1
Order By: Relevance
“…Several previous studies investigated the associations between adiposity indices and BMD or osteoporosis, but the findings were inconsistent [11][12][13]18]. In agreement with our findings, a cohort of 16,500 women aged 50 years and older found high BMD in the highest BMI values (≥30 kg/ m 2 ) [11].…”
Section: Comparison With Other Studiessupporting
confidence: 79%
See 1 more Smart Citation
“…Several previous studies investigated the associations between adiposity indices and BMD or osteoporosis, but the findings were inconsistent [11][12][13]18]. In agreement with our findings, a cohort of 16,500 women aged 50 years and older found high BMD in the highest BMI values (≥30 kg/ m 2 ) [11].…”
Section: Comparison With Other Studiessupporting
confidence: 79%
“…During July 2015 and September 2017, 39,259 participants aged 18-79 years old were recruited from five counties of Henan province to the Henan Rural Cohort Study and finished the baseline survey. Detailed baseline characteristics had been described in a previous study [18]. Only 8475 participants who completed the BMD measurement were included in our present study.…”
Section: Study Participantsmentioning
confidence: 99%
“…Weight, height, and waist circumference (WC) were measured twice for each person to the nearest 0.5 kg and 0.1 cm, according to a standard protocol. Body mass index (BMI) was calculated as weight divided by square of height (kg/m 2 ) . The blood pressure was measured three times with a 30‐second interval between each measurement using an electronic sphygmomanometer (HEM‐770AFuzzy, Omron, Japan) in sitting position, and the mean value was obtained .…”
Section: Methodsmentioning
confidence: 99%
“…The rates of abdominal obesity still increased rapidly in the Chinese population, especially in rural population 57 . The agestandardized prevalence of abdominal obesity was 43.71% in the general Chinese rural adults 58 . Thus, effective measures should be taken to improve the status of prevention and control of abdominal obesity to improve the status of ICH.In addition, we found that drinking may be associated with a more ideal CVH and a more ideal HF in women, but not in men.…”
Section: Discussionmentioning
confidence: 93%